Occurrence and assessment of antibiotic resistance and virulence of Enterococcus spp. strains isolated from fecal samples of wild animals - Krzysztof Skowron; Wiktor Borkowski; Natalia Wiktorczyk-Kapischke; Anna Budzyńska; Monika Wilk; Julia Czuba; Jan Fiderewicz; Joanna Skonieczna-Kurpiel; Katarzyna Grudlewska-Buda (Scientific Reports)
Abstract About 60% of the etiological agents of human infections are of animal origin, and the microorganisms causing them can be isolated not only from farmed and domestic animals, but also from wildlife. Enterococcus spp. may exhibit intrinsic or acquired resistance to many antibiotic groups, posing significant therapeutic challenges. The aim of this study was to identify and assess the antibiotic resistance and virulence genes of Enterococcus strains isolated from fecal samples of wild animals. The 118 strains were obtained from deer (n = 38), wild boar (n = 29), hare (n = 19), roe deer (n = 12), fallow deer (n = 5), raccoon dog (n = 4), fox (n = 4), moose (n = 2), polecat (n = 2), rabbit (n = 1), wolf (n = 1) and marten (n = 1). Antibiotic resistance assessments were performed using the disk diffusion method following the recommendations of the European Committee on Antimicrobial Susceptibility Testing (EUCAST). The frequency of occurrence of vancomycin-resistant enterococci (VRE) phenotypes, high-level streptomycin resistance (HLSR), high-level gentamicin resistance (HLGR), and high-level aminoglycoside resistance (HLAR) was also determined. The PCR was used to detect virulence genes (VGs) (agg, gelE, EfaAfs, ace, pil, ebpA, ebpB, ebpC, srtA, hyl, asa, cylA and cylB). The study revealed a high species diversity of Enterococcus spp. Among the 118 strains collected, 70 were resistant to at least one antibiotic. The majority of strains exhibited resistance to eravacycline, while the least resistance was observed against ampicillin. Strains with VRE, HLSR, HLGR, and HLAR phenotypes were identified. Multidrug resistant (MDR) strains were detected. However, extensively drug-resistant (XDR) and pandrug-resistant (PDR) strains were not observed. The virulence factors were present in the tested strains, and the most frequently detected gene was agg encoding aggregation substance. We have provided evidence that healthy wild animals can be reservoirs of pathogenic Enterococcus strains, including MDR strains and with many VGs, which can be transmitted to humans.